2005
DOI: 10.1128/iai.73.12.7887-7893.2005
|View full text |Cite
|
Sign up to set email alerts
|

Conjugates of Group A and W135 Capsular Polysaccharides ofNeisseria meningitidisBound to RecombinantStaphylococcus aureusEnterotoxin C1: Preparation, Physicochemical Characterization, and Immunological Properties in Mice

Abstract: Neisseria meningitidis groups A (GAM) and W135 capsular polysaccharides (CPs) were bound to recombinant Staphylococcus aureus enterotoxin C1 (rSEC). The CPs were activated with 1-cyano-4-dimethylaminopyridinium tetrafluoroborate and then bound to adipic acid dihydrazide derivatives of rSEC. Syntheses were conducted with native GAM CP (GAMP), W135 CP (W135P), and ultrasonicated or hydrazine-treated W135P at various concentrations of reactants, pHs, and ionic strengths. The conjugates were characterized by compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Although the natural occurrence of both O-acetylated and non-O-acetylated W and Y isolates has been demonstrated (i.e., in the UK with a predominance of non-O-acetylated W and O-acetylated Y strains [ 23 ], and during the Hajj outbreak where all the W strains were non-O-acetylated [ 24 ]), the currently licensed serogroup W and Y conjugate vaccines contain the O-acetylated CPS. The general role of O-acetylation of these CPSs is still debated, however several studies conducted in the preclinical stage and using human sera seem to confirm that there is no difference in functional activity of O-acetylated or non-O-acetylated CPSs [ 22 , 25 , 26 , 27 ]. By investigating the meningococcal Y antigen, Fusco et al [ 22 ] suggested that the O-acetyl groups may mask an important epitope to the immune system and thereby mislead the antibody response, resulting in an escape mechanism.…”
Section: O-acetylation In Conjugate Vaccinesmentioning
confidence: 99%
“…Although the natural occurrence of both O-acetylated and non-O-acetylated W and Y isolates has been demonstrated (i.e., in the UK with a predominance of non-O-acetylated W and O-acetylated Y strains [ 23 ], and during the Hajj outbreak where all the W strains were non-O-acetylated [ 24 ]), the currently licensed serogroup W and Y conjugate vaccines contain the O-acetylated CPS. The general role of O-acetylation of these CPSs is still debated, however several studies conducted in the preclinical stage and using human sera seem to confirm that there is no difference in functional activity of O-acetylated or non-O-acetylated CPSs [ 22 , 25 , 26 , 27 ]. By investigating the meningococcal Y antigen, Fusco et al [ 22 ] suggested that the O-acetyl groups may mask an important epitope to the immune system and thereby mislead the antibody response, resulting in an escape mechanism.…”
Section: O-acetylation In Conjugate Vaccinesmentioning
confidence: 99%
“…However, Vi is not suitable for routine immunization of infants and young children because of its age-related immunogenicity and T-cell independence. As was shown for other capsular polysaccharides, such as Haemophilus influenzae type b (8,37); meningococcus groups A, C, and W135; and Streptococcus pneumoniae (12,20), Vi covalently bound with protein conferred T-cell dependence and increased immunogenicity (48)(49)(50). To date, diphtheria toxoid (DT), tetanus toxoid (TT), cholera toxins (CT), the B subunit of the heat-labile toxin (LT-B) of Escherichia coli, recombinant outer membrane protein of Klebsiella pneumoniae (rP40), and iron-regulated outer-membrane proteins (IROMPs) of S. Typhi have served as carriers for Vi polysaccharide in laboratory studies (16, 17, 32, 48-50; personal communications).…”
mentioning
confidence: 99%
“…However, their data indicate that for some sera the agreement in anti-OAc+ vs. anti OAc- W IgG assignments was serum-specific and did not reflect the in vitro functional (killing) activity. Jin et al 68 analyzed the immunogenicity of MenW polysaccharide conjugated to Staphylococcus enterotoxin C1 having low levels of O-acetylation in mice; removal of these O-acetyl moieties had no adverse effect on the observed immunogenicity.…”
Section: Polysaccharidesmentioning
confidence: 99%